2019
DOI: 10.18632/oncotarget.26583
|View full text |Cite
|
Sign up to set email alerts
|

LATS1/2 kinases trigger self-renewal of cancer stem cells in aggressive oral cancer

Abstract: Cancer stem cells (CSCs), which play important roles in tumor initiation and progression, are resistant to many types of therapies. However, the regulatory mechanisms underlying CSC-specific properties, including self-renewal, are poorly understood. Here, we found that LATS1/2, the core Hippo pathway-kinases, were highly expressed in the oral squamous cell carcinoma line SAS, which exhibits high capacity of CSCs, and that depletion of these kinases prevented SAS cells from forming spheres under serum-free cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Likewise, LATS1 and LATS2 expression was comparable among epithelial, intermediate, and mesenchymal ovarian cancer cell lines, indicating that LATS protein expression was not associated with the cells’ EMT status. This is at odds with the view that LATS expression declines when cells transition from epithelial to mesenchymal (Nozaki et al 2019; Moroishi et al 2015; Lei et al 2008). Opposed to these studies is a report showing that LATS can potentiate tumor-promoting factors and augment EMT (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, LATS1 and LATS2 expression was comparable among epithelial, intermediate, and mesenchymal ovarian cancer cell lines, indicating that LATS protein expression was not associated with the cells’ EMT status. This is at odds with the view that LATS expression declines when cells transition from epithelial to mesenchymal (Nozaki et al 2019; Moroishi et al 2015; Lei et al 2008). Opposed to these studies is a report showing that LATS can potentiate tumor-promoting factors and augment EMT (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…To validate these previous data, we investigated LATS expression (1) and clinical outcome in ovarian cancer using various publicly accessible transcriptomic data sets and (2) in our Swiss ovarian cancer patient cohort and related the results to various clinicopathological parameters. As LATS expression has also been shown to regulate epithelial-mesenchymal transition (EMT), a cellular program that promotes invasion and metastasis during cancer development, and modulate drug responses (Nozaki et al 2019; Zhang et al 2012; Takahashi et al 2007; Kawahara et al 2008), we determined LATS protein expression in a panel of ovarian cancer cell lines and investigated (3) whether LATS expression in these cell lines was an indicator for the EMT state of the cells and for the sensitivity to chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of our findings is further supported by a research study demonstrating that CHK1 inhibitors in combination with chemotherapy dramatically reduced CSC survival in vitro by inducing premature cell cycle progression and mitotic catastrophe in non-small cell lung cancer 46 . Additionally, another study proved that knockdown of CHK1 successfully inhibited sphere formation of CSCs in the absence of cisplatin in aggressive oral cancer 47 . Consistently, we found that upregulation of CHK1 can increase the sphere formation capacity of ovarian CSCs without cisplatin treatment ( Figure 5 B ), which may be due to the reduction of DNA damage caused by other external factors.…”
Section: Discussionmentioning
confidence: 97%
“…Cancer stem cells are important in driving therapy resistance and transcription factors associated with pluripotency, specifically Nanog, Oct4 and Sox2, have been associated with aggressive PC [108]. In other cancers, deletion of LATS and the resultant up-regulation in YAP/TAZ activity resulted in uncontrolled expansion of Sox2-positive cells [109], whilst LATS1/2 activity can trigger self-renewal of cancer stem cells in aggressive oral cancer [110]. Therefore, it would be interesting to investigate the levels of Hippo pathway activity in this subgroup of patients with high expression of Oct 4, Sox2 and Nanog.…”
Section: Self-renewalmentioning
confidence: 99%